(untitled) (diségno, 2019)
The city of Padua is surveyed by technicians coordinated by Giovanni Valle, who elaborates, draws and ‘amends’, under the direction of Simone Stratico –whose role has not yet been clarified [1]– a map that was engraved in Rome, within 1784, by Giovanni Volpato. For technical reasons the huge surface of the drawing is transfered on 20 copper plates of various sizes [Ghironi, Mazzi 1985] becoming, in its original edition, one of the most important and famous maps of the city. Realized according to precise criteria of geometric measurement, it can be considered, therefore, a punctual record of the urban condition of Padua in the 18th century [Zaggia 2009]. (read more)